Fish biodiversity research in the Mekong Basin - Baran, Eric; Chum, N.; Fukushima, M.; Hand,T.; Hortle, K.G.; Jutagate, T.; Kang, B. (Springer, 2012)
The Mekong River is one of the great rivers of the world and is characterized by high fish biodiversity (Valbo-Jorgensen et al. 2009). The Mekong region is in fact a fish biodiversity hotspot whose richness is only now being revealed. During the last decade more than 279 new species of fish have been discovered in this basin alone (WWF 2009). An analysis of fish species present in 204 rivers worldwide recorded in FishBase (www.fishbase.org) (Fig. 1) and backed by a scientific study or publication. Baran (2010) recently showed that the Mekong River is the second richest river in the world for its fish diversity, after the Amazon River.